Implementation of a Multi-Level Approval System in the Vendor Management System (VMS) to Strengthen Vendor Verification at PT X - Dandi Nurrachim; Murti Widyaningsih (Journal of Social Research, 2026)
This research aims to analyze the effect of implementing the tiered approval system on strengthening vendor verification within the Vendor Management System (VMS) platform at PT X. The research employs a quantitative approach by distributing questionnaires to 30 respondents directly involved in the procurement and vendor verification process. The research instrument was tested for validity and reliability, with all items found to be valid and highly reliable (? = 0.934). The results of the linear regression analysis indicate that the implementation of the tiered approval system has a positive and significant effect on strengthening vendor verification, as evidenced by a t-count value of 14.173 > t-table and a significance level of 0.001. The 87.3% contribution rate demonstrates that the tiered approval system plays an important role in improving data accuracy, transparency, and accountability in the verification process. The study suggests enhancing digital infrastructure to accelerate approval workflows and providing regular user training to optimize VMS-based verification controls.